Domestic plant food loss and waste in the United States: Environmental footprints and mitigation strategies. (1st August 2022) - Sun, Huihui; Sun, Yanchen; Jin, Mingzhou; Ripp, Steven A.; Sayler, Gary S.; Zhuang, Jie
Highlights: Food losses and waste (FLW) mitigation should be prioritized on vegetables. Vegetable FLW contributes 29% of total plant FLW-wasted blue water. Vegetable FLW contributes 50% of total plant FLW-emitted carbon dioxide. Vegetable FLW is mainly driven by urbanization, income, and gross domestic product. Abstract: The United States (U.S.) aims to reduce half of food loss and waste (FLW) by 2030. To achieve this goal, the public, academic, and political attentions on FLW have been increasing, and a series of actions have been implemented. However, the actions lack consideration on the categorical priority of FLW mitigation in relation to environmental footprints. In this article, we compare the FLW of three main plant food categories (i.e., grains, vegetables, and fruits) and their water and carbon footprints during 1970–2017. The vegetable FLW doubled during the period, reaching 3.39 × 10 10 kg in 2017, which was 5- and 2-fold higher than the FLW of grains and fruits, respectively. The FLW of vegetables, grains, and fruits contributed 29%, 47%, and 24% to the total blue water wasted through FLW. The total carbon dioxide emissions generated by plant FLW were contributed by vegetables with 50%, grains with 31%, and fruits with 19%. Canonical correspondence analysis indicates that vegetable FLW had a higher positive correlation with urbanization, household incomes, gross domestic product, and high-income population than grain FLW, whereas fruit FLW was not influenced by these socioeconomic factors. Therefore, we suggest that the FLW mitigation should be prioritized on vegetables. Specific strategies include local food sourcing, shortening food miles, building food belts, and developing controlled-environment agriculture. Our data-based comparisons provide valuable insights into food policy improvement for achieving the 2030 reduction goal of the U.S., but the insights could be improved by considering the influences of foods imported from other nations.